The true costs of food in Kenya and Viet Nam - Benfica, Rui; Davis, Kristin E. (Canva, 2024)
The CGIAR Nature-Positive Solutions Initiative (NATURE+) aims to re-imagine, co-create, and implement nature-positive agrifood systems that equitably support local food and livelihoods, while ensuring that agriculture is a net positive contributor to nature and the environment.